Association between antibiotic residues, antibiotic resistant bacteria and antibiotic resistance genes in anthropogenic wastewater – An evaluation of clinical influences. (February 2020) - Voigt, A.M.; Zacharias, N.; Timm, C.; Wasser, F.; Sib, E.; Skutlarek, D.; Parcina, M.; Schmithausen, R.M.; Schwartz, T.; Hembach, N.; Tiehm, A.; Stange, C.; et al.
Abstract: The high use of antibiotics in human and veterinary medicine has led to a wide spread of antibiotics and antimicrobial resistance into the environment. In recent years, various studies have shown that antibiotic residues, resistant bacteria and resistance genes, occur in aquatic environments and that clinical wastewater seems to be a hot spot for the environmental spread of antibiotic resistance. Here a representative statistical analysis of various sampling points is presented, containing different proportions of clinically influenced wastewater. The statistical analysis contains the calculation of the odds ratios for any combination of antibiotics with resistant bacteria or resistance genes, respectively. The results were screened for an increased probability of detecting resistant bacteria, or resistance genes, with the simultaneous presence of antibiotic residues. Positive associated sets were then compared, with regards to the detected median concentration, at the investigated sampling points. All results show that the sampling points with the highest proportion of clinical wastewater always form a distinct cluster concerning resistance. The results shown in this study lead to the assumption that ciprofloxacin is a good indicator of the presence of multidrug resistant P. aeruginosa and extended spectrum β-lactamase (ESBL)-producing Klebsiella spec., Enterobacter spec. and Citrobacter spec., as it positively relates with both parameters. Furthermore, a precise relationship between carbapenemase genes and meropenem, regarding the respective sampling sites, could be obtained. These results highlight the role of clinical wastewater for the dissemination and development of multidrug resistance. Highlights: Clinically influenced wastewater differs from municipal wastewater (WW). Statistical associations between antibiotics and resistant bacteria are observed. Ciprofloxacin seems to be an indicator for the presence of ESBL-producing bacteria. P. aeruginosa, resistant against 3rd gen. cephalosporins, were mainly in clinical WW.